Nasal Physiology and Pathophysiology of Nasal Disorders 2013
DOI: 10.1007/978-3-642-37250-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Nose and Sleep Breathing Disorders

Abstract: • The nose is the input channel for the airfl ow. Its rigid and erectile structures determine the outline and the output of the airfl ow in the upper airway. Nose obstruction, due to reversible or nonreversible factors, produces collapsing forces that are manifest downstream in the collapsible pharynx. Moreover, nose pathologies result in unstable oral breathing, decreased activation of nasalventilatory refl ex and reduced lung nitric oxide. Long-term oral breathing impacts on the craniofacial growth. The mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…We demonstrated that allergens have a significant effect preferentially on the REM‐RDI independent of all‐night AHI, RDI, and REM‐AHI. Earlier studies have concluded that nasal congestion in AR is a primary contributor to the increase in the number of apneic episodes, RERAs, and microarousals that cause sleep disturbances . In children with AR and moderate to severe OSA, a significantly elevated AHI was seen during REM sleep .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We demonstrated that allergens have a significant effect preferentially on the REM‐RDI independent of all‐night AHI, RDI, and REM‐AHI. Earlier studies have concluded that nasal congestion in AR is a primary contributor to the increase in the number of apneic episodes, RERAs, and microarousals that cause sleep disturbances . In children with AR and moderate to severe OSA, a significantly elevated AHI was seen during REM sleep .…”
Section: Discussionmentioning
confidence: 94%
“…We had hypothesized that already inflamed situationally paralyzed upper airway structures would preferentially narrow air passages during REM due to REM stage–specific skeletal muscle atonia. Despite the pharynx often being focused on as the primary area of obstruction in OSA, upstream nasal resistance can limit downstream pharyngeal airflow . Throughout human evolution, narrowing of the upper aerodigestive tract compensated for the predisposition to speech and language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired nasal ventilatory reflex reduces spontaneous ventilation [23,28] causing failure of activation of the UA dilator muscles [23]. This condition worsens apnoea episodes because UA dilator muscle tone is inhibited, consequently reducing breathing and minute lung ventilation [16,17,24,29].…”
Section: Impaired or Absent Nasal Ventilatory Reflexmentioning
confidence: 99%